PELAKSANAAN PENCEGAHAN DAN PENGENDALIAN INFEKSI (PPI) DI PUSKESMAS TEMANGGUNG SELAMA MASA PANDEMI COVID-19 - Ahmad, Nurul Fauziah; Budiyanti, Rani Tiyas; Fatmasari, Eka Yunila (Jurnal Kesehatan Masyarakat, 2023)
The spread of COVID-19 has also affected primary health services, including the Puskesmas Temanggung, or Indonesian Primary Health Care which is located in Temanggung Regency, Central Java Province. Based on the regulation of the Minister of Health Number 43 of 2019 concerning Community Health Centers, it is known that the Puskesmas, is responsible for implementing health policies, including policies for preventing and controlling COVID-19 infections. The research, which was conducted from October to November 2022, adapted a qualitative research design with an analytic descriptive approach. Based on this research, it was found that the communication aspects that affected Infection Prevention and Control, namely transmission, clarity and consistency, were good. While in the aspect of resources found deficiencies in infrastructure and capabilities of human resources. Dispositional aspects are less found in implementing commitment. Meanwhile, in the aspect of bureaucratic structure, there are deficiencies in the Standart Operating Procedure (SOP) for several precautions.